The Concept of “Meta” Education on Islamic Values Based on the Psychological Development of Cadet - Mustofa, Imron; Hadi, Abd. (IAIN Ponorogo, 2024)
This study investigates meta-consciousness cultivation based on Islamic principles among Naval Academy cadets. These principles symbolize military virtues in society. The study explores integrating multicultural Islamic values into cadets and the subsequent internalization of these values in developing meta-consciousness. A qualitative approach focusing on phenomenological analysis was employed to address this issue by analyzing various textual and contextual sources. Data were obtained through in-depth interviews with several individuals in the Academy. In addition, the study investigated curriculum-related documents and educational programs. The collected data were thoroughly analyzed using data reduction, presentation, and deduction. The results were then compared with findings from related studies to validate the conclusions. This study obtained two primary findings. Firstly, the Academy perceived Islamic brotherhood as solidarity within a multicultural environment. This solidarity was described by three fundamental principles: self-regulation, tolerance, and ukhūwah. In our observation, the Academy provided immersive experiences while upholding professionalism, ethics, and reverence for diversity. It emphasized its dedication to nurturing a holistic comprehension and implementing multicultural Islamic values among its cadets. Secondly, this research found that the Academic embraced the instructional system design (ISD) framework to instill “meta” Islamic values in individual mindsets.